The Effect of Digital Financial Literacy and Digital Financial Inclusion on Women’s Entrepreneurship Empowerment - Syahnur, Khaerunnisa Nur Fatimah; Syarif, Rahmat; Arianti (Jurnal Manajemen Bisnis, 2024)
The majority of the contributions of entrepreneurs to the Indonesian economy come from small and medium-sized enterprises (SMEs), and female entrepreneurs dominate 99% of UMKM in Indonesia. Women entrepreneurs face the challenge of being able to survive the evolution of the digital age. Women entrepreneurs have a high level of digital inclusion but have low literacy, making them vulnerable to fraud. The relationship of women with the digital world is still far from ideal. Therefore, this study aims to test the impact of digital financial literacy and digital financial inclusion on the empowerment of women entrepreneurs. The study uses a survey method with a sample of female entrepreneurs in South Sulawesi Province. Respondents of this study represented 7 districts or cities spread across the South Sulawesi Province. The results of this study prove that digital financial literacy and digital financial inclusion have a significant positive impact on the empowerment of women entrepreneurs. Female entrepreneurs very much need digital literacy and financial inclusion in view of the very rapid digital development. This research responds to the urgency of research topics on literature and financial inclusion with digital concepts that are still very limited in Indonesia.